Thermal properties of PCM microcapsules modified polymer coatings - Tan, Carine. (2013)
Microencapsulated phase change material (microPCM) has been widely used as a thermal energy storage, waste heat utilization and space heating and cooling. Microcapsules prevent encapsulated PCM from leaking during its phase change and also provide a larger heat transfer area per unit volume to heat storage vessel. Thermal conductivity of these microPCM is an important property to be studied. This study uses paraffin wax as the core material and urea-formaldehyde polymer as the shell material. Microcapsules are synthesized by in-situ polymerization. Effects of carbon nanotubes (CNTs) on thermal performance and thermal conductivity of the microcapsules and its samples are studied. Size distribution and surface morphology of microcapsules are characterized by optical and scanning electron microscopy (SEM). SEM analysis showed that the microcapsules have a rough and porous outer surface and is spherical in shape, with a shell wall thickness of 3μm. Addition of CNTs further increased the size of the microcapsules. Thermal properties of the microcapsules and its samples are carried out by Thermo-Gravimetric Analyzer (TGA) and Differential Scanning Calorimetry (DSC). TGA results presented a high decomposition temperature of the microcapsules. Contrariwise, addition of CNTs decreased the decomposition temperature of the microcapsules by approximately 20oC. DSC results showed that microcapsules have a energy storage capacity of around 70-80J/g and epoxy-microPCM samples have 8% of the microcapsules’ energy storage capacity. CNTs help to increase the energy storage capacity of both microcapsules and samples. Epoxy and epoxy-microPCM samples are tested for its thermal conductivity. Results demonstrated that increased thickness of the sample and decreased PCM concentration increases the sample’s thermal conductivity. Mixing high thermal conductivity additive, CNTs in PCM is an appropriate method to improve the thermal conductivity of epoxy-microPCM samples by about 10%. The conclusion can also be drawn that CNTs brought about significant benefits to the microcapsules and its samples. Recommendations for future work are presented as well.